(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Social protection of the population becomes a priority of the state policy due to its mass impoverishment, caused by military actions, high inflation rate, sharp increase the cost of communal services and low wages. The efficiency of spent of the money in this direction affects not only the well-being of the average family, but also the state of social security from the nano to the regional and national levels. Therefore, the purpose of the article is to analyze the trends of social protection of the population of the Volyn region, identify problems and their impact on the level of social security of the population and the state as a whole. The methodology of the research is based on general scientific methods of generalization, induction and deduction, theoretical and statistical analysis, as well as a systematic approach. The article investigated the trends of social protection of Volyn region. The program of housing subsidies, payment of state social assistance, sanatorium-and-spa treatment, preferential support, arrears of wages and it’s level, social protection of the population as a whole and its specific categories were analyzed. The social work of orphanages, regional social service centers, centers of social services for families, children, and youth, and so on was valued. It is determined that from the state and local budgets huge funds are spent on social protection of the population. However, this social policy is not effective, as it does not cover all those who need protection, and forces the working population to seek state assistance. In order not to allow an increase the social tensions, and to ensure an adequate level of social security, it is necessary to: systematically raise the level of minimum wages, thereby reducing the contingent of recipients of social subsidies and allowances; transfer all available benefits in cash form; improve, consolidate and ensure interoperability of all registers of socially vulnerable populations in order to provide a simplified procedure for obtaining social guarantees and attach them to a specific person. The main challenges and priorities of social protection were selected and also their influence was based on the social security of the region and of the state as a whole. It have practical significance and can be used by public authorities, local self-government and social protection to build effective social policies.